2019
DOI: 10.1097/sla.0000000000003450
|View full text |Cite
|
Sign up to set email alerts
|

A Clinical Nomogram for Predicting Node-positive Disease in Esophageal Cancer

Abstract: Objective:We developed and validated a nomogram predicting the likelihood of occult lymph node metastases in surgically resectable esophageal cancers.Background:Patients with esophageal cancer with positive lymph nodes benefit from neoadjuvant therapy, but limitations in current clinical staging techniques mean nodal metastases often go undetected preoperatively.Methods:The National Cancer Database was queried for patients with clinical T1-3N0M0 cancer undergoing upfront esophagectomy from 2004 to 2014. Multiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
52
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(55 citation statements)
references
References 22 publications
3
52
0
Order By: Relevance
“…Thus far, a few researchers have developed nomogram models to predict the risk of LNM in esophageal cancer [6,11,[24][25][26]. For example, Zheng et al [11] recently developed a nomogram for the prediction of LNM in early-stage ESCC patients.…”
Section: Discussionmentioning
confidence: 99%
“…Thus far, a few researchers have developed nomogram models to predict the risk of LNM in esophageal cancer [6,11,[24][25][26]. For example, Zheng et al [11] recently developed a nomogram for the prediction of LNM in early-stage ESCC patients.…”
Section: Discussionmentioning
confidence: 99%
“…The main advantages of this study include: rst, a nomogram was built for the prediction for the development of POP, with good accuracy according to the statistical veri cations. As a graphical presentation of predictive model, nomogram has been widely used in the area of oncology [25][26][27][28], with great advantages such as easy operation, convenience and effectiveness. Previously, we have reported the predictive nomogram for the development of postoperative delirium in elderly patients with a hip fracture [29].…”
Section: Discussionmentioning
confidence: 99%
“…Kaplan‐Meier survival curves demonstrated that cases with elevated CABYR‐a/b level have much poorer OS and DFS than those with downregulated CABYR‐a/b level and TCGA database provided similar results. Multivariate analysis and prognostic nomograms, especially the latter, play vital role in evaluating the prognostic impact in cancer . Nomograms, graphic representations of complicated mathematical formulas, was broadly applied as prognostic models to analyze an individual's predicted prognosis by incorporating multiple and detailed prognostic parameters .…”
Section: Discussionmentioning
confidence: 99%
“…Multivariate analysis and prognostic nomograms, especially the latter, play vital role in evaluating the prognostic impact in cancer. 17 Nomograms, graphic representations of complicated mathematical formulas, was broadly applied as prognostic models to analyze an individual's predicted prognosis by incorporating multiple and detailed prognostic parameters. [18][19][20] In the present study, according to the multivariate analysis, CABYR-a/b-based nomograms were created to interpret the predictive role of CABYRa/b.…”
Section: Discussionmentioning
confidence: 99%